Perwujudan Prinsip Umum WTO dan Prinsip Resiprositas Dalam Kesepakatan Dagang Tiongkok Fase Pertama - Veronika, Cresta Violy; Yustisia Utami, Putu Devi (Kertha Wicara : Journal Ilmu Hukum, 2020)
This article aims to analyze about international trade principles that enacted in GATT 1944 with correlation in  trade agreement made by US-China as countries with strong economical state. This article contains analysis about the fulfillment of  the reciprocity principle between US-China trade agreement. This article uses normative legal method with statute approach that refer to Economic and Trade Agreement Between the United States of America and The People’s Republic of China (Phase One). The absence of the reciprocity principle in this agreement is contained in  section 6 Article 6.2 concerning in Expanding Trade. This article mentions a clause about the  obligation for China to comply in import purchases toward US’s product. This statement shows an  imbalance with the purchase of China’s product conducted by US. The authors found that the fulfillment of the reciprocity principle in accordance with GATT 1944 did not fully accomplished. Thus, the application of this agreement does not obtain a maximum profits between two parties as the purpose of applying reciprocity principle in international trade. Key Words : Trade Agreement, Reciprocity Principle, International Trade